Does tuberculosis remain a social problem? - Batura-Gabryel, Halina (Przewodnik Lekarza/Guide for GPs, 2006)
With approximately 3 million annual deaths, tuberculosis (TB) remains a leading cause of mortality worldwide into the 21st century. It is estimated that one third of the world population harbor a latent infection by the causative pathogen, Mycobacterium tuberculosis . In this paper are presented TB risk factors, last world and polish epidemiological data and some social reasons of increasing number of people with this disease.